1988
DOI: 10.1029/ja093ia11p12932
|View full text |Cite
|
Sign up to set email alerts
|

A general association between discrete auroras and ion precipitation from the tail

Abstract: Using two‐dimensional observations from the spinning, polar‐orbiting S3‐3 satellite, we have compared the locations of regions that we identify as discrete auroral arcs with regions of isotropic ion precipitation. Regions of discrete auroral arcs are defined to be regions containing particle distributions consistent with field‐aligned potential drops ≳0.5 kV. Polar cap arcs and local times near noon (0900‐1500 MLT) are excluded from this study. Our most important result is that the inferred locations of discre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 29 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…They found bursts of the low-energetic (<20-keV) electrons, which they associated with discrete auroras, to be embedded into the region where both energetic electrons and energetic protons were isotropic. Lyons et al (1988) found the low-energy electron precipitation bursts to be located in the poleward part of the isotropic proton precipitation. Our results con®rm these ®ndings.…”
Section: 3mentioning
confidence: 99%
See 2 more Smart Citations
“…They found bursts of the low-energetic (<20-keV) electrons, which they associated with discrete auroras, to be embedded into the region where both energetic electrons and energetic protons were isotropic. Lyons et al (1988) found the low-energy electron precipitation bursts to be located in the poleward part of the isotropic proton precipitation. Our results con®rm these ®ndings.…”
Section: 3mentioning
confidence: 99%
“…Our results con®rm these ®ndings. Lyons et al (1988) suggested that the proton isotropy is produced by the particle scattering in the current-sheet region, thus concluding that the discrete aurora originate from the farthest part of the magnetotail. This led them to the conclusion that discrete aurora are from the PSBL.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…Arcs are a pervasive morphology, occurring at essentially all local times (e.g. Stringer and Belon (1967); Gustafsson (1967)), from the poleward boundary of the oval equatorward to the proton and/or electron isotropic boundaries (Lyons et al, 1988;Yahnin et al, 1997). Statistical studies indicate that arc occurrence peaks on the night side (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown by Lyons and Evans [1984] and Lyons et al [1988] that discrete aurora, in general, occur in regions of nonadiabatic ion behavior on the nightside, rather than in regions of nonadiabatic electron behavior. In contrast, dayside nonadiabatic ion behavior may be associated with electron aurora [Lyons et al, 1987].…”
Section: Imi Strawman Instrumentsmentioning
confidence: 99%